Charge transport at a molecular GaAs nanoscale junction. (6th July 2018) - Vezzoli, Andrea; Brooke, Richard J.; Ferri, Nicolò; Brooke, Carly; Higgins, Simon J.; Schwarzacher, Walther; Nichols, Richard J.
Abstract : The use of semiconducting electrodes in molecular junctions is an elegant way to impart new properties to nanodevices. Here we report metal-molecule(s)–metal Schottky photodiodes whose behaviour can be tuned by appropriate choice of molecule and doping density, giving further insights into the molecule–semiconductor interface. Abstract : In recent years, the use of non-metallic electrodes for the fabrication of single-molecule junctions has developed into an elegant way to impart new properties to nanodevices. Integration of molecular junctions in a semiconducting platform would also speed technological deployment, as it would take advantage of established industrial infrastructures. In a previous proof-of-concept paper, we used simple α, ω-dithiol self-assembled monolayers on a gallium arsenide (GaAs) substrate to fabricate molecular Schottky diodes with a STM. In the devices, we were also able to detect the contribution of a single-molecule to the overall charge transport. The prepared devices can also be used as photodiodes, as GaAs is a III–V direct bandgap (1.42 eV at room temperature) semiconductor, and it efficiently absorbs visible light to generate a photocurrent. In this contribution, we demonstrate that fine control can be exerted on the electrical behaviour of a metal-molecule–GaAs junction by systematically altering the nature of the molecular bridge, the type and doping density of the semiconductor and the light intensity and wavelength. Molecular orbital energy alignment dominates the charge transport properties, resulting in strongly rectifying junctions prepared with saturated bridges ( e.g. alkanedithiols), with increasingly ohmic characteristics as the degree of saturation is reduced through the introduction of conjugated moieties. The effects we observed are local, and may be observed with electrodes of only a few tens of nanometres in size, hence paving the way to the use of semiconducting nanoelectrodes to probe molecular properties. Perspectives of these new developments for single molecule semiconductor electrochemistry are also discussed.